2008
DOI: 10.1258/acb.2008.008037
|View full text |Cite
|
Sign up to set email alerts
|

Audit of acute hypoglycaemia in children: re-audit of procedures for diagnosis

Abstract: The new hypopack protocol has increased the number of appropriately performed investigations. Provision of information concerning dextrose infusion has assisted the interpretation of the hypopack results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…A premade pack containing the required specimen tubes and biochemistry request forms, is one method to potentially improve the adequacy of investigation of hypoglycaemia 9. These ‘Hypoglycaemia packs’ contain all the relevant equipment and therefore aim to facilitate complete and timely investigations.…”
Section: Discussionmentioning
confidence: 99%
“…A premade pack containing the required specimen tubes and biochemistry request forms, is one method to potentially improve the adequacy of investigation of hypoglycaemia 9. These ‘Hypoglycaemia packs’ contain all the relevant equipment and therefore aim to facilitate complete and timely investigations.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Children tend to present with IKH between the ages of 18 months and seven years, 58 the commonest time when hypoglycaemic episodes are observed. 16,17 The exact pathogenesis of IKH is unknown; however, Bodamer et al 68 have shown using isotope studies that it may be due to a failure to maintain hepatic glucose production and not increased glucose oxidation. More recently Huidekoper et al 67 have supported this view and hypothesized that IKH may represent 'the lower tail of the Gaussian distribution of fasting intolerance in children'.…”
Section: Lang Investigating Hypoglycaemia In Childhoodmentioning
confidence: 99%
“…These initial investigations should provide information concerning intermediate metabolites and other diagnostic markers and allow the investigator to decide on further investigations and management options. 17 Numerous hospitals also have preprepared packs containing the appropriate specimen tubes for the investigation of hypoglycaemia in the wards and accident and emergency departments, termed 'hypopacks'. 16 If used properly, these packs can assist with the investigation and management of a child with suspected hypoglycaemia.…”
Section: Laboratory Investigation Of Hypoglycaemiamentioning
confidence: 99%
See 2 more Smart Citations